Comparison between Real Time PCR and Gel based PCR Technique in Diagnosis Y Chromosome microdeletions in infertile azoospermia males in the Iraqi Kurdish Population - Muhsin Jamil Abdulwahid; Mustafa Saber Al-Attar (BioMed Target Journal)
Infertility is a disorder of the reproductive system characterized by a couple's inability to conceive after at least one year of regular, unprotected sexual activity. Approximately 15% of couples worldwide struggle with infertility. Male infertility accounts for 20–30% of all infertility cases and is defined as the inability of a male to achieve conception in a healthy, fertile female. Azoospermia factor (AZF) genes are located on the long arm of the human Y chromosome and are involved in spermatogenesis. Microdeletions in the AZF region are now recognized as the second most prevalent genetic cause of spermatogenetic failure and male infertility. This study aims to diagnose AZF deletions in 289 males with infertile azoospermia and 50 males with fertile sperm using two PCR techniques, real-time PCR and gel-based PCR, and compare the results of both techniques. In diagnosing AZF deletions, the results of both real-time PCR and gel-based PCR are identical. Generally AZF deletion found in 10 patients (3.5%), three of them (30%) had microdeletions in the AZFc region, 3 of them (30%) had microdeletions in the AZFb region, also other 3 patients had microdeletions in the b and c of AZF (AZF b,c) region, and the final one patient (10%) had microdeletions in the all a, b and c (AZF a,b,c) region. According to the findings of this study, there are no distinctions between both techniques for diagnosing AZF deletion in males with infertility.